Maternal and fetal outcome in cases of eclampsia - Dodiya, Hetal N.; Shah, Sapana R.; Vyas, Rupa C.; Parikh, Purvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Eclampsia refers to occurrence of generalized tonic clonic convulsions (GTCS) followed by confusion or coma during pregnancy or puerperium in patients with preeclampsia excluding other neurological conditions. Purpose of this study was to evaluate the risk factors, management protocols and determine maternal and perinatal morbidity and mortality in patients of eclampsia. Methods: This is retrospective study of 180 cases of eclampsia carried out from June 2017 to December 2019 including all the antepartum, intrapartum and postpartum cases at tertiary care centre. Immediate management was focused to control the convulsion and lower the blood pressure followed by NST and USG foetus with Doppler study. Results: In this study, 72.2% cases reported antepartum eclampsia while 27.8% cases were postpartum and overall incidence was 0.91% of total deliveries conducted during the study period. Incidence was higher in primigravida (74.4%) and below 25 years age (68.8%). Magnesium sulphate was effective in 94.4% cases. Study reports 63 normal vaginal delivery, 5 assisted vaginal delivery, 110 caesarean section and 2 women expired undelivered. There were 10 maternal deaths. Conclusions: Time interval between eclamptic seizures and initiation of therapy is an important prognostic factor affecting maternal and perinatal outcome. Public awareness regarding the importance of regular antenatal visits can help in reducing chances of development of eclampsia. Even though various drugs and methods have been tried for the treatment of eclampsia, the definitive management is the delivery of foetus after control of convulsion, hypertension and should be managed at tertiary care hospital.